In Vitro Cloning and Stem Cutting of Stevia (Stevia Rebaudiana Bertoni.) for Mass Propagation in Chittagong, Bangladesh - Islam, S.A.M Nurul; Tareq, Saiful Alam M (The International Journal of Biotechnology, 2015)
Stevia (Stevia rebaudiana Bertoni.) is non-caloric sweetening plant. It was cloned using shoot tip in vitro MS medium supplemented with 6-Benzyl Amino Purine (BAP) and Kinetin (Kn). Excised shoots were rooted in half strength Murashige and Skoog (MS) medium supplemented with Indole-3 Butyric Acid (IBA). The rooted plantlets were transferred to soil and coconut husk filled bags and beds. Stem cutting method in sand medium with water misting propagation bed without plant growth regulator was effective for mass propagation. The plantlets derived from in vitro and stem-cutting grew luxuriantly in cultivating field during long day months (March to September) and produced gregarious flowering during short day months(October to February). Similar type of flowering behavior was observed between these two types of propagules of Stevia.